Effect of alcohol–gasoline blends optimization on fuel properties, performance and emissions of a SI engine. (1st January 2015) - Masum, B.M.; Masjuki, H.H.; Kalam, M.A.; Palash, S.M.; Habibullah, M.
Abstract: This study, as an observation, put its utmost effort to emphasize on the development of various physicochemical properties using multiple alcohols (C2 to C6 ) at different ratios compared to that of the conventional ethanol–gasoline blend. To optimize the properties of multiple alcohol–gasoline blends, properties of each fuel were measured first. An optimization tool of Microsoft Excel "Solver" was used for obtaining the optimum blend. Using optimizing tool, three optimum blend ratios were selected which possessed maximum heating value (MaxH), maximum research octane number (MaxR) and maximum petroleum displacement (MaxD). These blends were used for testing in a four cylinder gasoline engine at the wide open throttle condition with varying speeds and compared obtained outcomes with that of E15 (15% ethanol and 85% gasoline) as well as gasoline. Optimized blends have shown higher brake torque and brake thermal efficiency (BTE) but lower brake specific fuel consumption (BSFC) than E15. MaxR, MaxD and MaxH blends produced mean 4.4%, 1.8% and 0.4% increased BTE and mean 4.39%, 1.8% and 2.27% lower BSFC than that of E15. On the other hand, MaxR, MaxD, MaxH and E15 reduced 4.46%, 8.37%, 12.4% and 17.2%, mean CO emission and 4.5%, 11.81%, 8.19% and 16% mean HC emission respectively than that of gasoline. NOx emission of optimized blends was higher than gasoline. However, MaxR, MaxD, MaxH reduced 4%, 14.57% and 20.76% NOx than that of E15. Highlights: Optimized C2 –C6 alcohols–gasoline blends achieved better properties than E15. Optimum blends improved BTE and torque and reduced BSFC than that of E15 fuel. Compared to gasoline, optimum blends reduced CO and HC emission. Optimum fuels reduced NOx emission than E15 fuel.